Stents

JP7642015B2Active Publication Date: 2025-03-07BIOTYX MEDICAL (SHENZHEN) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023076688
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-11-27
Filing Date
2023-05-08
Publication Date
2025-03-07
Estimated Expiration
2039-10-14

AI Technical Summary

Benefits of technology

【0016】 試験によると、植込み型機器の金属基体の肉厚さに基づいて、粒子状物質の寸法及び平均含有量を適正に制御することにより、金属基体の微細構成を最適化させ、植込み型機器の塑性変形能力を高めることに役立ち、植込み型機器が異常に破壊されてしまうリスクを低下させることができるということを証明することが可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007642015000003
    Figure 0007642015000003
  • Figure 0007642015000004
    Figure 0007642015000004
  • Figure 0007642015000005
    Figure 0007642015000005
Patent Text Reader

Abstract

To provide a stent having comparatively good plastic deformation capability.SOLUTION: A stent that includes a metallic substrate 100 and satisfies the following condition contains a particulate matter having a dimension of 1 μm or more in the metallic substrate, the particulate matter contains an impurity introduced from the outside or contains an inherent impurity and a second phase, the thickness of the metallic substrate is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 15 μm or less, the theoretical excess extension capability of the metallic substrate is 25-45%, the average content of the particulate matter is 20 ppm or less, the average content of the particulate matter being an area occupied by the particulate matter in the metallic substrate 100 per unit area, provided that when N is defined as the theoretical excess extension capability of the metallic substrate, L is defined as a length when one wavy ring 110 in the metallic substrate is made completely straight, and D is defined as a nominal outer diameter of the metallic substrate, the following expression is satisfied.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of invasive medical devices, in particular implantable devices. [Background technology]

[0002] Vascular stents are mesh-like or tubular implantable medical devices used to treat various vascular diseases. By being implanted into the affected area, vascular stents support the narrowed or blocked area of ​​the blood vessel, reduce elastic retraction and remodeling of the blood vessel, and maintain smooth blood flow into the lumen.

[0003] Vascular stents are generally made of metal or polymer materials. Vascular stents are generally formed by cutting or braiding, and then need to be pressed against a delivery balloon or reduced into a delivery sheath to be fixed to a delivery system. In this process, the outer diameter of the stent may be reduced by 50% or more, resulting in relatively large deformation. When the vascular stent is delivered to the affected area, the vascular stent is released and expanded so that the outer diameter of the vascular stent is expanded by 200% or more again, resulting in further large deformation. In the process of pressing and expanding, the vascular stent is repeatedly subjected to large deformation. Moreover, when the stent is implanted in the body, bending, extension, and even twisting may occur in the blood vessel due to the movement of the blood vessel and the contraction and expansion of the blood vessel. The stent is subjected to cyclic loads in the blood vessel (e.g., compression of the artery in the radial direction, tension and bending in the axial direction, etc.). It is desirable for the stent to have a high plastic deformation ability. However, the current stent does not have sufficient plastic deformation ability, so when the stent is implanted, it will be broken due to fatigue, and even during the expansion process, it will be broken. In this case, bad results will occur, firstly, the broken stent rod will locally cause mechanical irritation to the blood vessel, inflammation and neointimal proliferation, and secondly, the broken stent rod will locally destroy the stent structure, causing thrombosis and blood flow blockage, affecting the blood flow supply to organs. This not only causes the local area of ​​the stent to lose the radial support function, but also makes it difficult to achieve the radial support function, which may bring about a very large clinical risk to patients. Summary of the Invention [Problem to be solved by the invention]

[0004] The plastic deformation capacity of a vascular stent is mainly related to its structural design and the material of the stent. When the structural design of a stent is made, the plastic deformation capacity of the material itself plays a relatively large role. The plastic deformation capacity of a metal-based material is determined by its microstructure. The microstructure includes the size and orientation of crystal grains, the metallographic structure, the particulate matter of the second phase, and the structure of dislocations. Since the plastic deformation capacity corresponding to different microstructures also differs greatly, it is possible to optimize the microstructure to optimize the plastic deformation capacity of the material. [Means for solving the problem]

[0005] In view of this, there is a need to provide an implantable device that has relatively good plastic deformation capabilities.

[0006] An implantable device comprising a metal substrate, the metal substrate containing particulate matter having a size of 1 μm or greater; the thickness of the metal substrate is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 15 μm or less, and the average content of the particulate matter is 40 ppm or less; When the thickness of the metal substrate is greater than 0.12 mm and not greater than 0.2 mm, the maximum dimension of the particulate matter is not greater than 20 μm and the average content of the particulate matter is not greater than 100 ppm; When the thickness of the metal substrate is greater than 0.2 mm and not greater than 0.3 mm, the maximum dimension of the particulate matter is not greater than 25 μm and the average content of the particulate matter is not greater than 220 ppm.

[0007] In one embodiment, the thickness of the metal substrate is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 10 μm or less, and the average content of the particulate matter is 40 ppm or less; When the thickness of the metal substrate is greater than 0.12 mm and less than 0.2 mm, the maximum dimension of the particulate matter is less than 15 μm and the average content of the particulate matter is less than 100 ppm; When the thickness of the metal substrate is greater than 0.2 mm and not greater than 0.3 mm, the maximum dimension of the particulate matter is not greater than 20 μm and the average content of the particulate matter is not greater than 220 ppm.

[0008] In one embodiment, the thickness of the metal substrate is 0.04 mm or more and 0.12 mm or less, the maximum size of the particulate matter is 10 μm or less, and the average content of the particulate matter is 20 ppm or less; When the thickness of the metal substrate is greater than 0.12 mm and not greater than 0.2 mm, the maximum dimension of the particulate matter is not greater than 15 μm and the average content of the particulate matter is not greater than 50 ppm; When the thickness of the metal substrate is greater than 0.2 mm and not greater than 0.3 mm, the maximum dimension of the particulate matter is not greater than 20 μm, and the average content of the particulate matter is not greater than 110 ppm.

[0009] In one embodiment, the thickness of the metal substrate is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 15 μm or less, and the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is 20 ppm or less; the thickness of the metal substrate is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 15 μm or less, and the theoretical overexpansion capacity of the metal substrate is greater than 45%, the average content of the particulate matter is 40 ppm or less; The thickness of the metal substrate is greater than 0.12 mm and less than 0.2 mm, the maximum dimension of the particulate matter is less than 20 μm, and the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is less than 50 ppm; the wall thickness of the metal substrate is greater than 0.12 mm but not greater than 0.2 mm, the maximum dimension of the particulate matter is less than 20 μm, and the theoretical overexpansion capacity of the metal substrate is greater than 45%, the average content of the particulate matter is less than 100 ppm; The thickness of the metal substrate is greater than 0.2 mm and less than 0.3 mm, the maximum dimension of the particulate matter is less than 25 μm, and the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is less than 110 ppm; When the thickness of the metal substrate is greater than 0.2 mm but not greater than 0.3 mm, the maximum dimension of the particulate matter is less than 25 μm, and the theoretical overexpansion capacity of the metal substrate is greater than 45%, the average content of the particulate matter is less than 220 ppm.

[0010] In one embodiment, the thickness of the metal substrate is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 15 μm or less, and the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is 10 ppm or less; the thickness of the metal substrate is 0.04 mm or more and 0.12 mm or less; the maximum dimension of the particulate matter is 15 μm or less; and the theoretical overexpansion capacity of the metal substrate is greater than 45%; the average content of the particulate matter is 20 ppm or less; The thickness of the metal substrate is greater than 0.12 mm and less than 0.2 mm, the maximum dimension of the particulate matter is less than 20 μm, and the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is less than 25 ppm; the wall thickness of the metal substrate is greater than 0.12 mm but not greater than 0.2 mm, the maximum dimension of the particulate matter is less than 20 μm, and the theoretical overexpansion capacity of the metal substrate is greater than 45%, the average content of the particulate matter is less than 50 ppm; The thickness of the metal substrate is greater than 0.2 mm and less than 0.3 mm, the maximum dimension of the particulate matter is less than 25 μm, and the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is less than 55 ppm; When the thickness of the metal substrate is greater than 0.2 mm but not greater than 0.3 mm, the maximum dimension of the particulate matter is less than 25 μm, and the theoretical overexpansion capacity of the metal substrate is greater than 45%, the average content of the particulate matter is less than 110 ppm.

[0011] In one embodiment, the thickness of the metal substrate is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 10 μm or less, and the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is 10 ppm or less; the thickness of the metal substrate is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 10 μm or less, and the theoretical overexpansion capacity of the metal substrate is greater than 45%, the average content of the particulate matter is 20 ppm or less; The thickness of the metal substrate is greater than 0.12 mm and less than 0.2 mm, the maximum dimension of the particulate matter is less than 15 μm, and the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is less than 25 ppm; the wall thickness of the metal substrate is greater than 0.12 mm but not greater than 0.2 mm, the maximum dimension of the particulate matter is less than 15 μm, and the theoretical overexpansion capacity of the metal substrate is greater than 45%, the average content of the particulate matter is less than 50 ppm; The thickness of the metal substrate is greater than 0.2 mm and not greater than 0.3 mm, the maximum dimension of the particulate matter is not greater than 20 μm, and the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is not greater than 55 ppm; When the thickness of the metal substrate is greater than 0.2 mm but not greater than 0.3 mm, the maximum dimension of the particulate matter is less than 20 μm, and the theoretical overexpansion capacity of the metal substrate is greater than 45%, the average content of the particulate matter is less than 110 ppm.

[0012] In one embodiment, the material of the metal substrate is one selected from the group consisting of iron nitride, pure iron, cobalt chromium alloy, and magnesium alloy.

[0013] In one embodiment, the implantable device is a vascular stent, a biliary stent, an esophageal stent, or a urethral stent.

[0014] In one embodiment, the vascular stent is a coronary vascular stent or a peripheral vascular stent.

[0015] In one embodiment, the material of the metal substrate is produced by a process of electroslag remelting and then a process of vacuum arc remelting. Effect of the Invention

[0016] Tests have shown that, based on the thickness of the metal substrate of the implantable device, by properly controlling the size and average content of the particulate matter, the microstructure of the metal substrate can be optimized, which helps to improve the plastic deformation ability of the implantable device, and reduces the risk of abnormal fracture of the implantable device. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a schematic diagram showing the configuration of a metal substrate of an implantable device according to one embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing the metal base of the implantable device shown in FIG. 1 developed in the axial direction. [Diagram 3] FIG. 2 is a scanning electron microscope (SEM) image of a fracture in a coronary vascular stent according to Example 2. [Figure 4] FIG. 13 is a scanning electron microscope (SEM) image of a fractured portion in a coronary artery stent according to Comparative Example 1. [Diagram 5] FIG. 11 is a scanning electron microscope (SEM) image of a fractured portion in a coronary artery stent according to Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] In order to facilitate an understanding of the invention, the present invention will now be generally described with reference to the accompanying drawings, in which preferred embodiments of the present invention are shown. However, the present invention may be embodied in many different forms and is not limited to the embodiments set forth herein. On the contrary, these embodiments are provided to provide a clear and comprehensive understanding of the teachings of the present invention.

[0019] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. The terms used herein are merely for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any combination or any combination of one or more associated items.

[0020] In this context, the dimension of a particulate matter means the maximum distance between two points on the periphery of the particulate matter in the same plane.

[0021] In one embodiment of the implantable device, the implantable device is a vascular stent, a biliary stent, an esophageal stent or a urethral stent. In one embodiment, the vascular stent is a coronary vascular stent or a peripheral vascular stent.

[0022] As shown in FIG. 1, the implantable device includes a metal substrate 100, which is of a skeletonized luminal configuration.

[0023] 2, the metal substrate 100 includes a plurality of wavy rings 110 arranged in an axial direction Y, and a connecting means 120 connecting two adjacent wavy rings 110. The wavy rings 110 include a plurality of wave configurations 112 arranged in a circumferential direction Z.

[0024] The metal substrate 100 is made of a metal material. In one embodiment, the metal substrate 100 is made of one of iron nitride, pure iron, cobalt chromium alloy, and magnesium alloy. It can be understood that in other embodiments, the metal substrate 100 may be made of other metals or alloys than the above-listed metals or alloys, and any metal or alloy that meets the requirements of implantable devices and has relatively good biocompatibility with the living body may be used.

[0025] The material forming the metal substrate 100 contains a plurality of particulate matter, so that a plurality of particulate matter having a size of 1 μm or more is formed on the metal substrate 100. However, the particulate matter may include impurities introduced from the outside, or may include endogenous impurities or second phases. The particulate matter may be derived from foreign matter introduced during the process of smelting the metal material. For example, during the process of smelting steel material, oxides or silicates are formed by the addition of deoxidizers, or during the process of solidifying steel, sulfides or nitrides are formed due to the decrease in solubility of certain elements (e.g., sulfur and nitrogen), and these particulate matter are left in the steel as they are because they cannot be discharged in time. It is difficult to completely avoid the formation of particulate matter, and it is difficult to accurately control the distribution of the particulate matter because the particulate matter is randomly distributed.

[0026] The size and content of the particulate matter have a negative effect on forming the microstructure of the metal substrate 100, and to a certain extent, adversely affect the plastic deformation ability of the metal substrate 100. The degree of the adverse effect is mainly related to the distribution of the particulate matter and the size of the particulate matter. If the particulate matter is distributed in the area where the metal substrate 100 is seriously deformed, it is more likely to cause the implantable device to be abnormally destroyed. The larger the size of the particulate matter, the more serious the destruction of the continuity of the material, and the more likely it is to cause the implantable device to be abnormally destroyed. Therefore, controlling the particulate matter can reduce the risk of destroying the implantable device. Therefore, it is necessary to reduce the content of the particulate matter, because the lower the content of the particulate matter, the lower the probability of it being distributed in the deformed area of ​​the implantable device, and the less the harm it causes.

[0027] Regarding the size of the particulate matter, the smaller the size of the particulate matter, the less the material continuity is broken, and the less the harm. Moreover, the smaller the size of the implantable device, the smaller the size of the particulate matter required. Especially in the field of vascular stents, the current trend is to design thin walls, so the thinner the wall thickness, the more necessary it is to control the size of the particulate matter. Research has found that, for particulate matter in metal-based materials, when the size of the particulate matter is less than 1 μm, these submicron or nanoscale particulate matter basically have no effect on the plastic deformation ability of the material, and can even play the role of strengthening and increase the strength of the material. However, when the size of the particulate matter is more than 1 μm, the particulate matter may break the continuity of the broken material, reducing the plasticity, toughness and fatigue performance of the material, and when these particulate matter appear at the deformation positions of the metal substrate 100, the metal substrate 100 is very prone to abnormal fracture (e.g., fracture occurs during expansion) at these positions. It is therefore necessary to control the size and content of particulate matter having a size of 1 μm or greater.

[0028] In one embodiment, when the thickness of the metal substrate 100 is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 15 μm or less and the average content of the particulate matter is 40 ppm or less. When the thickness of the metal substrate 100 is greater than 0.12 mm and not greater than 0.2 mm, the maximum dimension of the particulate matter is not greater than 20 μm, and the average content of the particulate matter is not greater than 100 ppm. The metal substrate 100 has a thickness greater than 0.2 mm and not greater than 0.3 mm, the maximum dimension of the particulate matter is not greater than 25 μm, and the average content of the particulate matter is not greater than 220 ppm.

[0029] In one embodiment, when the thickness of the metal substrate 100 is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 10 μm or less and the average particulate matter content is 40 ppm or less. When the thickness of the metal substrate 100 is greater than 0.12 mm and not greater than 0.2 mm, the maximum dimension of the particulate matter is not greater than 15 μm, and the average content of the particulate matter is not greater than 100 ppm. When the thickness of the metal substrate 100 is greater than 0.2 mm and not greater than 0.3 mm, the maximum dimension of the particulate matter is not greater than 20 μm, and the average content of the particulate matter is not greater than 220 ppm.

[0030] In one embodiment, when the thickness of the metal substrate 100 is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 10 μm or less and the average content of the particulate matter is 20 ppm or less. When the thickness of the metal substrate 100 is greater than 0.12 mm and not greater than 0.2 mm, the maximum dimension of the particulate matter is not greater than 15 μm, and the average content of the particulate matter is not greater than 50 ppm. When the thickness of the metal substrate 100 is greater than 0.2 mm and not greater than 0.3 mm, the maximum dimension of the particulate matter is not greater than 20 μm, and the average content of the particulate matter is not greater than 110 ppm.

[0031] In one embodiment, the thickness of the metal substrate 100 is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 15 μm or less, and the theoretical overexpansion capacity of the metal substrate 100 is 25-45%, and the average particulate matter content is 20 ppm or less. When the wall thickness of the metal substrate is greater than or equal to 0.04 mm and less than or equal to 0.12 mm, the maximum dimension of the particulate matter is less than or equal to 15 μm, and the theoretical overexpansion capacity of the metal substrate 100 is greater than 45%, the average particulate matter content is less than or equal to 40 ppm. When the thickness of the metal substrate 100 is greater than 0.12 mm and less than 0.2 mm, the maximum dimension of the particulate matter is less than 20 μm, and the theoretical overexpansion capacity of the metal substrate 100 is 25-45%, the average content of the particulate matter is less than 50 ppm. When the thickness of the metal substrate 100 is greater than 0.12 mm but not greater than 0.2 mm, the maximum dimension of the particulate matter is less than 20 μm, and the theoretical overexpansion capacity of the metal substrate 100 is greater than 45%, the average particulate matter content is less than 100 ppm. When the thickness of the metal substrate 100 is greater than 0.2 mm and less than 0.3 mm, the maximum dimension of the particulate matter is less than 25 μm, and the theoretical overexpansion capacity of the metal substrate 100 is 25-45%, the average particulate matter content is less than 110 ppm. When the thickness of the metal substrate 100 is greater than 0.2 mm but not greater than 0.3 mm, the maximum dimension of the particulate matter is less than 25 μm, and the theoretical overexpansion capacity of the metal substrate 100 is greater than 45%, the average particulate matter content is less than 220 ppm.

[0032] In one embodiment, the thickness of the metal substrate 100 is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 15 μm or less, and the theoretical overexpansion capacity of the metal substrate 100 is 25-45%, and the average particulate matter content is 10 ppm or less. When the thickness of the metal substrate 100 is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 15 μm or less, and the theoretical overexpansion capacity of the metal substrate 100 is greater than 45%, the average content of the particulate matter is 20 ppm or less. When the thickness of the metal substrate 100 is greater than 0.12 mm and less than 0.2 mm, the maximum dimension of the particulate matter is less than 20 μm, and the theoretical overexpansion capacity of the metal substrate 100 is 25-45%, the average particulate matter content is less than 25 ppm. When the thickness of the metal substrate 100 is greater than 0.12 mm but not greater than 0.2 mm, the maximum dimension of the particulate matter is less than 20 μm, and the theoretical overexpansion capacity of the metal substrate 100 is greater than 45%, the average particulate matter content is less than 50 ppm. When the thickness of the metal substrate 100 is greater than 0.2 mm and less than 0.3 mm, the maximum dimension of the particulate matter is less than 25 μm, and the theoretical overexpansion capacity of the metal substrate 100 is 25-45%, the average particulate matter content is less than 55 ppm. When the thickness of the metal substrate 100 is greater than 0.2 mm but not greater than 0.3 mm, the maximum dimension of the particulate matter is less than 25 μm, and the theoretical overexpansion capacity of the metal substrate 100 is greater than 45%, the average particulate matter content is less than 110 ppm.

[0033] In one embodiment, the thickness of the metal substrate 100 is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 10 μm or less, and the theoretical overexpansion capacity of the metal substrate 100 is 25-45%, and the average particulate matter content is 10 ppm or less. When the thickness of the metal substrate 100 is greater than or equal to 0.04 mm and less than or equal to 0.12 mm, the maximum dimension of the particulate matter is less than or equal to 10 μm, and the theoretical overexpansion capacity of the metal substrate 100 is greater than 45%, the average particulate matter content is less than or equal to 20 ppm. When the thickness of the metal substrate 100 is greater than 0.12 mm and less than 0.2 mm, the maximum dimension of the particulate matter is less than 15 μm, and the theoretical overexpansion capacity of the metal substrate 100 is 25-45%, the average particulate matter content is less than 25 ppm. When the thickness of the metal substrate 100 is greater than 0.12 mm but not greater than 0.2 mm, the maximum dimension of the particulate matter is less than 15 μm, and the theoretical overexpansion capacity of the metal substrate 100 is greater than 45%, the average particulate matter content is less than 50 ppm. When the thickness of the metal substrate 100 is greater than 0.2 mm and less than 0.3 mm, the maximum dimension of the particulate matter is less than 20 μm, and the theoretical overexpansion capacity of the metal substrate 100 is 25-45%, the average particulate matter content is less than 55 ppm. When the thickness of the metal substrate 100 is greater than 0.2 mm but not greater than 0.3 mm, the maximum dimension of the particulate matter is less than 20 μm, and the theoretical overexpansion capacity of the metal substrate 100 is greater than 45%, the average particulate matter content is less than 110 ppm. JPEG0007642015000001.jpg30170

[0034] Here, the nominal outer diameter is the nominal diameter of the metal substrate 100 plus twice the wall thickness. The nominal diameter is the expanded inner diameter of the metal substrate 100 (the inner diameter of the metal substrate 100 when implanted in a blood vessel and expansion is complete). When the nominal diameter is expressed according to the stent standard, for example, in the case of a 30008 standard stent, the expanded nominal diameter is 3 mm and the nominal length is 8 mm, in the case of a 27538 standard stent, the expanded nominal diameter is 2.75 mm and the nominal length is 38 mm, and in the case of a 35015 standard stent, the expanded nominal diameter is 3.5 mm and the nominal length is 15 mm.

[0035] The average content of particulate matter in the metal substrate 100 is the area of ​​the metal substrate 100 that is occupied by particulate matter within the metal substrate 100 per unit area. In other words, the average content of particulate matter in the metal substrate 100 = area occupied by particulate matter within the inspection area / area of ​​the inspection area. However, the area of ​​the inspection area is the total area of ​​the inspection area, and the area occupied by particulate matter within the inspection area is the area of ​​the inspection area that is randomly measured when the area is magnified 500 times by a scanning electron microscope and the area is 10 mm 2 The area of ​​the particulate matter in the detection area is equal to or larger than 5 mm. There are at least two detection areas, which are distributed on two mutually perpendicular planes in the metal substrate 100, and the detection area of ​​each detection area is 5 mm. 2 That is, the average particulate matter content = the total area occupied by particulate matter in multiple inspection areas / the total area of ​​multiple inspection areas.

[0036] The larger the size of the particulate matter, the larger the quantity of particulate matter and the larger the area of ​​the particulate matter per unit area in the metal substrate 100. When the average content of the particulate matter is determined and the size of the particulate matter is relatively large, the quantity of the particulate matter is small. Then, the probability that the particulate matter will appear at the critical deformation position is small, and the adverse effect on the plastic deformation of the implantable device is small. However, when the average content of the particulate matter is determined and the quantity of the particulate matter is relatively large, the size of the particulate matter is small, and even if the particulate matter appears at the critical deformation position, the adverse effect on the plastic deformation of the implantable device is relatively small. Therefore, by appropriately controlling the size of the particulate matter and the content of the particulate matter, the adverse effect of the particulate matter on the plastic deformation ability of the implantable device can be avoided.

[0037] In one embodiment, the material of the metal substrate 100 is produced by at least one of electroslag remelting and vacuum arc remelting. The particulate matter in the metal substrate 100 mainly comes from the raw material, and the level (size and average content) of the particulate matter is not essentially affected during the process of producing the metal substrate 100. Therefore, it is necessary to control the level of the particulate matter in the raw material. The electroslag remelting and vacuum arc remelting can increase the purity of the metal material, reduce the level of the particulate matter in the metal material, optimize the microstructure of the metal material, and thus optimize the plastic deformation ability of the metal material.

[0038] Electroslag remelting is a process in which an electrode is melted using resistance heat generated by the slag using an electric current as a heat source, the molten metal is converged into droplets, which pass through the slag layer and enter a molten metal pool. In the process of passing through the slag layer, non-metallic impurities are absorbed by the slag, and harmful elements (phosphorus, sulfur, lead, antimony, bismuth, tin, etc.) are effectively removed by the reaction between the molten steel and the molten slag and high-temperature vaporization, to refine an ingot, which is then finally solidified as a casting in a water-cooled crystallizer.

[0039] The vacuum arc remelting method is a smelting method in which the material to be melted is used as one electrode and a water-cooled copper crucible as the other electrode in a vacuum atmosphere. An arc is induced between the two electrodes, and the material to be melted is melted at high temperature by the arc and dripped into the crucible, where it gradually melts and condenses into an ingot. Melting and refining in a vacuum can significantly remove hydrogen and some volatile impurities, and the levitation effect can significantly reduce the particulate matter content.

[0040] In one embodiment, the material of the metal substrate 100 is first subjected to a process called electroslag remelting and then vacuum arc remelting to produce a high purity metal substrate 100. The first process, electroslag remelting, and then the second process, vacuum arc remelting, helps to reduce the particulate matter content.

[0041] It has been proven through testing that properly controlling the size of the particulate matter and the average content of the particulate matter based on the thickness of the metal substrate 100 of the implantable device can effectively avoid the adverse impact of the particulate matter in the material on the microstructure of the metal substrate 100, help improve the plastic deformation ability of the implantable device, and reduce the risk of abnormal fracture of the implantable device.

[0042] Furthermore, properly controlling the particulate size and average content based on the wall thickness of the metal substrate 100 and the theoretical over-expansion capacity of the metal substrate 100 can further optimize the microstructure of the metal substrate 100, thus enhancing the plastic deformation capacity of the implantable device.

[0043] The following is a section of specific examples (in the following examples, the above-mentioned implantable devices are described in more detail using a coronary artery stent and a peripheral vascular stent as examples, but the scope of protection of the present invention is not limited thereto).

[0044] The particulate matter referred to in the following examples is particulate matter having a size of 1 μm or more. For the manufacture of prototypes in the following examples, the material is polished or finished with a semi-automatic polishing machine called ECOMet250 manufactured by BRUKER to obtain a cross section with a mirror gloss, and then observed with a scanning electron microscope, or the prototype is placed in liquid nitrogen to perform brittle fracture to obtain a cross section, and then observed with a scanning electron microscope at a magnification of 500 times.

[0045] The effect of particulate matter on the plastic deformation capacity of the stent is evaluated by an expansion test. Some materials are randomly selected to make 3-tube materials or 3-filament materials, etc., to manufacture vascular stents. The length of the tube materials or filaments made from the selected materials is less than 1.0m. As long as the process requirements are met, these tube materials or filaments are made into stents as much as possible and an expansion test is carried out. After the stent is expanded to destruction, the fractured part is observed by a SEM scanning electron microscope produced by Nippon Co., Ltd. If no particulate matter is found at the fractured part, it means that the destruction of the stent is not caused by the influence of particulate matter, and the particulate matter in the material does not have a serious adverse effect on the plastic deformation capacity of the stent.

[0046] Example 1 The material is iron nitride, which is produced by electroslag remelting and then vacuum arc remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section, and the observation area is 15 mm 2 As a result, the maximum dimension of the particulate matter is 5 μm and the average content of the particulate matter is 5 ppm. When only three 1.0 m long tubes are made from some randomly selected materials to manufacture a coronary artery stent with a wall thickness of 0.040 mm, its theoretical overexpansion capacity is 60%. The manufactured coronary vascular stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0047] Example 2 The material is iron nitride, which is manufactured by electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section with an observation area of ​​10 mm2. 2 As a result, the maximum dimension of the particulate matter is 10 μm, the average content of the particulate matter is 10 ppm, and some materials are randomly selected to produce only three 1.2 m long tubes to produce a coronary artery stent with a wall thickness of 0.053 mm, and its theoretical overexpansion capacity is 51%. The manufactured coronary vascular stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0048] Example 3 The material is pure iron, manufactured by the vacuum arc remelting method. The material is placed in liquid nitrogen to cause brittle fracture, and a cross section is obtained. The observation area is 12 mm2. 2 As a result, the maximum dimension of the particulate matter is 10 μm, and the average particulate matter content is 40 ppm. Some materials are randomly selected to produce only three 1.5 m long tubes, and a coronary artery stent with a wall thickness of 0.070 mm is manufactured, and its theoretical overexpansion capacity is 65%. The manufactured coronary vascular stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0049] Example 4 The material was a cobalt-chromium alloy manufactured by electroslag remelting. A portion of the material was randomly cut and polished to obtain a shiny cross section with an observation area of ​​10 mm2. 2 As a result, the maximum dimension of the particulate matter is 15 μm, the average content of the particulate matter is 20 ppm, and some materials are randomly selected to produce only three 1.0 m long tubes to manufacture a coronary artery stent with a wall thickness of 0.080 mm, and its theoretical overexpansion capacity is 45%. The manufactured coronary vascular stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0050] Example 5 The material is iron nitride, which is produced by electroslag remelting and then vacuum arc remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section, with an observation area of ​​15 mm2. 2 As a result, the maximum dimension of the particulate matter is 5 μm, the average content of the particulate matter is 10 ppm, and some materials are randomly selected to produce only three 1.0 m long tubes and a 0.090 mm wall thickness coronary artery stent, and its theoretical overexpansion capacity is 36%. The manufactured coronary vascular stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0051] Example 6 The material is iron nitride, manufactured by a method called vacuum arc remelting. A portion of the material was randomly cut and polished to obtain a shiny cross section, with an observation area of ​​10 mm 2 As a result, the maximum dimension of the particulate matter is 5 μm, the average content of the particulate matter is 10 ppm, and some materials are randomly selected to produce only three 1.0 m long tubes to manufacture a coronary artery stent with a wall thickness of 0.100 mm, and its theoretical overexpansion capacity is 25%. The manufactured coronary vascular stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0052] Example 7 The material is a magnesium alloy manufactured by the vacuum arc remelting method. A portion of the material is randomly cut and polished to obtain a shiny cross section. The observation area is 10 mm2. 2As a result, the maximum dimension of the particulate matter is 10 μm, the average content of the particulate matter is 20 ppm, and some materials are randomly selected to produce only three 1.0 m long tubes to manufacture a coronary artery stent with a wall thickness of 0.120 mm, and its theoretical overexpansion capacity is 60%. The manufactured coronary vascular stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0053] Example 8 The material is iron nitride, manufactured by electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section. The observation area is 10 mm 2 As a result, the maximum dimension of the particulate matter is 10 μm, the average content of the particulate matter is 25 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.150 mm has a theoretical overexpansion capacity of 40%. The manufactured peripheral stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0054] Example 9 The material used was an iron nitride material manufactured by electroslag remelting. A portion of the material was randomly cut and polished to obtain a shiny cross section. The observation area was 10 mm2. 2 As a result, the maximum dimension of the particulate matter is 15 μm, the average content of the particulate matter is 50 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.180 mm has a theoretical overexpansion capacity of 50%. The manufactured peripheral stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0055] Example 10 The material used was a cobalt-chromium alloy manufactured by electroslag remelting. A portion of the material was randomly cut and polished to obtain a shiny cross section. The observation area was 10 mm2. 2 As a result, the maximum dimension of the particulate matter is 15 μm, the average content of the particulate matter is 60 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.190 mm has a theoretical overexpansion capacity of 45%. The manufactured peripheral stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0056] Example 11 The material is iron nitride, and is manufactured by a method called electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section, and the observation area is 10 mm 2 As a result, the maximum dimension of the particulate matter is 20 μm, the average content of the particulate matter is 100 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.200 mm has a theoretical overexpansion capacity of 65%. The manufactured peripheral stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0057] Example 12 The material is iron nitride, and is manufactured by a method called electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section, and the observation area is 10 mm 2As a result, the maximum dimension of the particulate matter is 10 μm, the average content of the particulate matter is 30 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.200 mm has a theoretical overexpansion capacity of 35%. The manufactured peripheral stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0058] Example 13 The material was pure iron, manufactured by electroslag remelting. A portion of the material was randomly cut and polished to obtain a shiny cross section, with an observation area of ​​10 mm 2 As a result, the maximum dimension of the particulate matter is 15 μm, the average particulate matter content is 80 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.200 mm has a theoretical overexpansion capacity of 65%. The manufactured peripheral stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0059] Example 14 The material is iron nitride, manufactured by electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section. The observation area is 10 mm 2 As a result, the maximum dimension of the particulate matter is 20 μm, the average particulate matter content is 55 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.230 mm has a theoretical overexpansion capacity of 60%. The manufactured peripheral stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0060] Example 15 The material is iron nitride, manufactured by electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section. The observation area is 10 mm 2 As a result, the maximum dimension of the particulate matter is 15 μm, the average particulate matter content is 110 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.280 mm has a theoretical overexpansion capacity of 50%. The manufactured peripheral stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0061] Example 16 The material is iron nitride, manufactured by electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section. The observation area is 10 mm 2 As a result, the maximum dimension of the particulate matter is 18 μm, the average particulate matter content is 40 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.290 mm has a theoretical overexpansion capacity of 45%. The manufactured peripheral stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0062] Example 17 The material is iron nitride, manufactured by electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section. The observation area is 10 mm 2 As a result, the maximum dimension of the particulate matter is 10 μm, the average content of the particulate matter is 20 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.300 mm has a theoretical overexpansion capacity of 25%. The manufactured peripheral stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0063] Example 18 The material is iron nitride, manufactured by electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section. The observation area is 10 mm 2 As a result, the maximum dimension of the particulate matter is 15 μm, the average particulate matter content is 60 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.300 mm has a theoretical overexpansion capacity of 35%. The manufactured peripheral stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0064] Example 19 The material is iron nitride, manufactured by electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section. The observation area is 10 mm 2 As a result, the maximum dimension of the particulate matter is 25 μm, the average particulate matter content is 220 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.300 mm has a theoretical overexpansion capacity of 65%. The manufactured peripheral stents were subjected to expansion testing and no particulate matter was found at the fracture site.

[0065] Comparison 1 The material is iron nitride, and the difference from Example 2 is that the average particle content is 50 ppm. Some materials were randomly selected, and only three tubular materials with a length of 1.2 m were produced to manufacture coronary artery stents similar to those in Example 2. The manufactured coronary artery vascular stent was subjected to an expansion test, and the results showed that particulate matter was found in all eight fractured parts of the coronary artery vascular stent. As shown in Figure 3, particulate matter is indicated by circles in Figure 3.

[0066] Comparison 2 The material is iron nitride, and the difference from Example 2 is that the maximum particle size is 20 μm. Some materials were randomly selected, and only three tubular materials with a length of 1.2 m were produced to manufacture coronary artery stents similar to those in Example 2. The manufactured coronary artery stent was subjected to an expansion test, and the results showed that particulate matter was found in all five fractured portions of the coronary artery stent. As shown in Figure 4, the particulate matter is indicated by a circle in Figure 4.

[0067] Comparison 3 The material is iron nitride, which is produced by electroslag remelting and then vacuum arc remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section, and the observation area is 15 mm2. 2 As a result, the maximum dimension of the particulate matter is 5 μm, the average content of the particulate matter is 25 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a coronary artery stent with a wall thickness of 0.090 mm has a theoretical overexpansion capacity of 36%. The manufactured coronary vascular stents were subjected to expansion testing, which resulted in particulate matter being found in six fractures in the coronary vascular stents.

[0068] Comparison 4 The material is iron nitride, which is produced by electroslag remelting and then vacuum arc remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section, and the observation area is 15 mm2. 2 As a result, the maximum dimension of the particulate matter is 20 μm, the average content of the particulate matter is 10 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a coronary artery stent with a wall thickness of 0.090 mm has a theoretical overexpansion capacity of 36%. The manufactured coronary vascular stents were subjected to expansion testing, which resulted in particulate matter being found in four fractures in the coronary vascular stents.

[0069] Comparison 5 The material used was an iron nitride material manufactured by electroslag remelting. A portion of the material was randomly cut and polished to obtain a shiny cross section. The observation area was 10 mm2. 2 As a result, the maximum dimension of the particulate matter is 15 μm, the average particulate matter content is 110 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.180 mm has a theoretical overexpansion capacity of 50%. The manufactured peripheral stents were subjected to expansion testing, which resulted in particulate matter being found in eight fractures in the peripheral stents.

[0070] Comparison 6 The material used was an iron nitride material manufactured by electroslag remelting. A portion of the material was randomly cut and polished to obtain a shiny cross section. The observation area was 10 mm2. 2 As a result, the maximum dimension of the particulate matter is 25 μm, the average content of the particulate matter is 50 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.180 mm has a theoretical overexpansion capacity of 50%. The manufactured peripheral stents were subjected to expansion testing, which resulted in particulate matter being found in eight fractures in the peripheral stents.

[0071] Comparison 7 The material is iron nitride, and is manufactured by a method called electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section, and the observation area is 10 mm2 As a result, the maximum dimension of the particulate matter is 10 μm, the average content of the particulate matter is 55 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.200 mm has a theoretical overexpansion capacity of 35%. The manufactured peripheral stents were subjected to expansion testing, which resulted in particulate matter being found in seven fractures in the peripheral stents.

[0072] Comparison 8 The material is iron nitride, and is manufactured by a method called electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section, and the observation area is 10 mm 2 As a result, the maximum dimension of the particulate matter is 25 μm, the average content of the particulate matter is 30 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.200 mm has a theoretical overexpansion capacity of 35%. The manufactured peripheral stents were subjected to expansion testing, which resulted in particulate matter being found in five fractures in the peripheral stents.

[0073] Comparison 9 The material is iron nitride, manufactured by electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section. The observation area is 10 mm 2 As a result, the maximum dimension of the particulate matter is 15 μm, the average particulate matter content is 120 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.300 mm has a theoretical overexpansion capacity of 35%. The manufactured peripheral stents were subjected to expansion testing, which resulted in particulate matter being found in 10 fractures in the peripheral stents.

[0074] Comparison 10 The material is iron nitride, manufactured by electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section. The observation area is 10 mm 2 As a result, the maximum dimension of the particulate matter is 30 μm, the average content of the particulate matter is 60 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.300 mm has a theoretical overexpansion capacity of 35%. The manufactured peripheral stents were subjected to expansion testing, which resulted in particulate matter being found in eight fractures in the peripheral stents.

[0075] Comparison 11 The material is iron nitride, manufactured by electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section. The observation area is 10 mm 2 As a result, the maximum dimension of the particulate matter is 15 μm, the average particulate matter content is 230 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.280 mm has a theoretical overexpansion capacity of 50%. The manufactured peripheral stents were subjected to expansion testing, which resulted in particulate matter being found in eight fractures in the peripheral stents.

[0076] Comparison 12 The material is iron nitride, which is manufactured by electroslag remelting. A portion of the material is randomly cut and polished to obtain a shiny cross section. The observation area is 10 mm2. 2As a result, the maximum dimension of the particulate matter is 30 μm, the average content of the particulate matter is 110 ppm, and some materials are randomly selected to produce three 1.0 m long tubes and a peripheral vascular stent with a wall thickness of 0.280 mm has a theoretical overexpansion capacity of 50%. The manufactured peripheral stents were subjected to expansion testing, which resulted in the discovery of particulate matter in eight fractures in the peripheral stents.

[0077] From the above examples and comparative examples, it can be seen that for vascular stents of different wall thicknesses, by controlling the level of particulate matter in the material, it is possible to avoid or reduce the adverse effect of particulate matter on the plastic deformation ability of the stent.

[0078] However, compared with Comparative Example 1, the average content of the particulate matter in Example 2 is lower, the probability of it appearing at key deformation positions is smaller, and the adverse effect on the plastic deformation ability of the stent is smaller; and compared with Comparative Example 2, the maximum dimension of the particulate matter in Example 2 is smaller, and the deterioration of the plastic deformation ability of the stent is smaller.

[0079] Compared with Comparative Example 3, the average content of the particulate matter in Example 5 is lower, the probability of it appearing at the key deformation position is smaller, and the adverse effect on the plastic deformation ability of the stent is smaller; and compared with Comparative Example 4, the maximum dimension of the particulate matter in Example 5 is smaller, and the deterioration of the plastic deformation ability of the stent is smaller.

[0080] Compared with Comparative Example 5, the average content of the particulate matter in Example 9 is lower, the probability of it appearing at key deformation positions is smaller, and the adverse effect on the plastic deformation ability of the stent is smaller; and compared with Comparative Example 6, the maximum dimension of the particulate matter in Example 9 is smaller, and the deterioration of the plastic deformation ability of the stent is smaller.

[0081] Compared with Comparative Example 7, the average content of particulate matter in Example 12 is lower, the probability of it appearing at key deformation positions is smaller, and the adverse effect on the plastic deformation ability of the stent is smaller; and compared with Comparative Example 8, the maximum dimension of the particulate matter in Example 12 is smaller, and the deterioration of the plastic deformation ability of the stent is smaller.

[0082] Compared with Comparative Example 9, the average content of particulate matter in Example 18 is lower, the probability of it appearing at key deformation positions is smaller, and the adverse effect on the plastic deformation ability of the stent is smaller; and compared with Comparative Example 10, the maximum dimension of the particulate matter in Example 18 is smaller, and the deterioration of the plastic deformation ability of the stent is smaller.

[0083] Compared with Comparative Example 11, the average content of particulate matter in Example 15 is lower, the probability of it appearing at key deformation positions is smaller, and the adverse effect on the plastic deformation ability of the stent is smaller; compared with Comparative Example 12, the maximum dimension of the particulate matter in Example 15 is smaller, and the deterioration of the plastic deformation ability of the stent is smaller.

[0084] The technical features in the embodiments described above may be combined in any manner. For the sake of brevity, all possible combinations of the technical features in the embodiments described above have been omitted, but as long as there is no contradiction in the combination of these technical features, any combination should be considered to be within the scope described in this specification.

[0085] The above-described examples are for illustrating some embodiments of the present invention, and although the description is detailed, it should not be understood as a limitation on the patent scope of the invention. What is described may be possible for a person skilled in the art to make other slight modifications and improvements without departing from the spirit of the present invention, all of which are included in the scope of protection of the present invention. Therefore, the scope of the patent of the present invention is subject to the scope of the attached claims.

Claims

1. A stent comprising a metal substrate, said stent satisfying the following conditions: The metal substrate contains particulate matter having a size of 1 μm or more, The particulate matter may contain exogenous impurities or may contain endogenous impurities or second phases; The average content of the particulate matter is the area of ​​the metal substrate 100 occupied by the particulate matter in the metal substrate per unit area, The metal substrate satisfies any one of the following conditions (1) to (6) depending on the thickness of the metal substrate, the maximum dimension of the particulate matter, and the theoretical overexpansion capacity: (1) The thickness of the metal substrate is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 15 μm or less, the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is 20 ppm or less; (2) The thickness of the metal substrate is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 15 μm or less, the theoretical overexpansion capacity of the metal substrate is greater than 45%, and the average content of the particulate matter is 40 ppm or less; (3) The thickness of the metal substrate is greater than 0.12 mm and less than or equal to 0.2 mm, the maximum dimension of the particulate matter is less than or equal to 20 μm, the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is less than or equal to 50 ppm; (4) The thickness of the metal substrate is greater than 0.12 mm and less than or equal to 0.2 mm, the maximum dimension of the particulate matter is less than or equal to 20 μm, the theoretical overexpansion capacity of the metal substrate is greater than 45%, and the average content of the particulate matter is less than or equal to 100 ppm; (5) The thickness of the metal substrate is greater than 0.2 mm and less than or equal to 0.3 mm, the maximum dimension of the particulate matter is less than or equal to 25 μm, the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is less than or equal to 110 ppm; (6) The thickness of the metal substrate is greater than 0.2 mm and less than 0.3 mm, the maximum dimension of the particulate matter is less than 25 μm, the theoretical overexpansion capacity of the metal substrate is greater than 45%, and the average content of the particulate matter is less than 220 ppm; where N is the theoretical overexpansion capacity of the metal substrate, L is the length of one wavy ring in the metal substrate when it is completely straightened, and D is the nominal outer diameter of the metal substrate. The stent is characterized in that

2. A stent according to claim 1, which satisfies any one of the following conditions (1) to (6) depending on a thickness of the metal substrate, a maximum dimension of the particulate matter, and a theoretical overexpansion capacity: (1) The thickness of the metal substrate is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 15 μm or less, the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is 10 ppm or less; (2) The thickness of the metal substrate is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 15 μm or less, the theoretical overexpansion capacity of the metal substrate is greater than 45%, and the average content of the particulate matter is 20 ppm or less; (3) The thickness of the metal substrate is greater than 0.12 mm and not greater than 0.2 mm, the maximum dimension of the particulate matter is not greater than 20 μm, the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is not greater than 25 ppm; (4) The thickness of the metal substrate is greater than 0.12 mm and less than or equal to 0.2 mm, the maximum dimension of the particulate matter is less than or equal to 20 μm, the theoretical overexpansion capacity of the metal substrate is greater than 45%, and the average content of the particulate matter is less than or equal to 50 ppm; (5) The thickness of the metal substrate is greater than 0.2 mm and not greater than 0.3 mm, the maximum dimension of the particulate matter is not greater than 25 μm, the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is not greater than 55 ppm; (6) A stent characterized in that the thickness of the metal substrate is greater than 0.2 mm and less than 0.3 mm, the maximum dimension of the particulate matter is less than 25 μm, the theoretical overexpansion capacity of the metal substrate is greater than 45%, and the average content of the particulate matter is less than 110 ppm.

3. The stent according to claim 1, which satisfies any one of the following conditions (1) to (6) depending on a wall thickness of the metal substrate, a maximum dimension of the particulate matter, and a theoretical overexpansion capacity: (1) The thickness of the metal substrate is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 10 μm or less, the theoretical overexpansion capacity of the metal substrate is 25 to 45%, and the average content of the particulate matter is 10 ppm or less; (2) The thickness of the metal substrate is 0.04 mm or more and 0.12 mm or less, the maximum dimension of the particulate matter is 10 μm or less, the theoretical overexpansion capacity of the metal substrate is greater than 45%, and the average content of the particulate matter is 20 ppm or less; (3) The thickness of the metal substrate is greater than 0.12 mm and less than or equal to 0.2 mm, the maximum dimension of the particulate matter is less than or equal to 15 μm, the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is less than or equal to 25 ppm; (4) The thickness of the metal substrate is greater than 0.12 mm and less than or equal to 0.2 mm, the maximum dimension of the particulate matter is less than or equal to 15 μm, the theoretical overexpansion capacity of the metal substrate is greater than 45%, and the average content of the particulate matter is less than or equal to 50 ppm; (5) The thickness of the metal substrate is greater than 0.2 mm and not greater than 0.3 mm, the maximum dimension of the particulate matter is not greater than 20 μm, the theoretical overexpansion capacity of the metal substrate is 25-45%, and the average content of the particulate matter is not greater than 55 ppm; (6) A stent characterized in that the thickness of the metal substrate is greater than 0.2 mm and less than 0.3 mm, the maximum dimension of the particulate matter is less than 20 μm, the theoretical overexpansion capacity of the metal substrate is greater than 45%, and the average content of the particulate matter is less than 110 ppm.

4. 2. The stent according to claim 1, wherein the material of the metal substrate is one selected from the group consisting of iron nitride, pure iron, cobalt-chromium alloy, and magnesium alloy.

5. 2. The stent of claim 1, wherein the stent is a vascular stent, a biliary stent, an esophageal stent or a urethral stent.

6. 6. The stent according to claim 5, wherein the vascular stent is a coronary vascular stent or a peripheral vascular stent.

7. A method for manufacturing the stent as described in claim 1, characterized in that the metal substrate material is produced by a vacuum arc remelting method after undergoing an electroslag remelting process.

Citation Information

Patent Citations

  • Magnesium alloy containing heavy rare earth elements

    JP2013524004A